2011
DOI: 10.1038/eye.2011.308
|View full text |Cite
|
Sign up to set email alerts
|

Visual function alterations in orbital tumors and factors predicting visual outcome after surgery

Abstract: Purpose To study the effect of orbital tumors on visual functions and highlight the factors predictive of visual outcome after surgery. Methods A prospective interventional study compared visual function parameters and fundus changes, before and after surgery, in eyes having well-defined orbital tumors with the normal fellow eye. These included visual acuity (VA), refractive error, keratometry changes, color vision, Goldmann visual field (GVF), and visual evoked response (VER). Results In total 28 cases (age r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Therefore, we concluded that myopic change was induced by AL elongation. However, in contrast to the presence of tumors, which induce astigmatism, 13,16 there were no significant changes in cylindrical refraction or axis in our study (Table 2), because orbital decompression symmetrically widened the space (Figure 2). We found no significant correlation between AL and exophthalmometric change (Figure 1b).…”
Section: Resultsmentioning
confidence: 39%
See 2 more Smart Citations
“…Therefore, we concluded that myopic change was induced by AL elongation. However, in contrast to the presence of tumors, which induce astigmatism, 13,16 there were no significant changes in cylindrical refraction or axis in our study (Table 2), because orbital decompression symmetrically widened the space (Figure 2). We found no significant correlation between AL and exophthalmometric change (Figure 1b).…”
Section: Resultsmentioning
confidence: 39%
“…Moreover, longstanding proptosis could result in permanent corneal shape changes. 13 Accordingly, corneal shape might not be affected by orbital decompression. In addition, results from the wavefront aberrometer showed that postsurgical changes in highorder aberration were not significant (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time they become larger and more pigmented, which facilitates identification (1,4) . Choroidal folds are not an unusual finding on fundus examination (5) and are the most prevalent finding in patients with orbital tumour (6) . They are usually asymptomatic but may cause visual disturbances such as hyperopia, astigmatism, and metamorphopsia (1,2,5) .…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Patients with folds caused by intraconal orbital tumours typically have hyperopia, while astigmatism is more common in those with extraconal tumours (6) .…”
Section: Clinical Aspectsmentioning
confidence: 99%